Direct and converse magnetoelectric effects in Metglas/LiNbO3/Metglas trilayers - Timopheev, A. A. (2013)
Electromechanical and magnetoelectric properties of Metglas/LiNbO3/Metglas trilayers have been studied in the frequency range from 20 Hz to 0.4 MHz. A trilayer of Metglas/PMN-PT/Metglas prepared in the same way was used as a reference. Though PMN-PT has much larger charge piezocoefficients than LiNbO3 (LNO), the direct magnetoelectric voltage coefficient is found to be comparable in both trilayers due to the much lower dielectric permittivity of LNO. The magnitude of the direct magnetoelectric effect in the LNO trilayers is about 0.4 V/cm Oe in the quasistatic regime and about 90 V/cm Oe at the electromechanical resonance. Calculations show that the magnetoelectric properties can be significantly improved (up to 500 V/cm Oe) via controlling the cut angle of LNO, choosing the appropriate thickness ratio of the ferroelectric/ferromagnetic layers and a better bonding between Metglas and LNO. Advantages of using LiNbO3-type ferroelectrics in magnetoelectric composites are discussed. (C) 2013 AIP Publishing LLC.